PENGARUH IRI HATI KEPADA REKAN KERJA TERHADAP WORK ENGAGEMENT YANG DIMEDIASI OLEH NEGATIVE FEELING PADA KARYAWAN PERBANKAN SYARIAH DI KOTA BANDA ACEH - Nur Annisa; Lenny Rakhmawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
The study aims to measure the effect of being envied by coworkers to work engagement with negative feeling as a mediating variable at one of sector financial in Banda Aceh city. The sample used in this study was employees in one of the Islamic banking in the city of Banda Aceh involving 144 respondens. Instrument used for data collecting was questionnaire. Simple random sampling was used as sampling technique. Hierarchical Regression Linear (HRL) was used as analysis method to determine the effect of variables involved. Based on the analysis results, it is indicated that being envied by coworkers influence work engagement and negative feeling as a mediate the relationship between envied by coworkers and work engagement.